2020
DOI: 10.1093/omcr/omaa092
|View full text |Cite
|
Sign up to set email alerts
|

Isolated tuberculosis of the spleen presenting with fever of unknown origin in a vaccinated child

Abstract: Tuberculosis (TB) is one of the top 10 causes of death worldwide and is more common in developing countries. Isolated splenic TB is typically found in trauma, miliary TB and immunocompromised status. We present a very rare case of an immunocompetent child with an isolated primary TB in the spleen. The child only had fever of unknown origin (FUO), and mild anaemia. The diagnosis was not made until splenectomy was performed. The patient took the quadruple therapy for TB, and follow-ups showed no recurrence. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…TB is a significant infectious disease that remains prevalent in resource-poor countries. While its incidence has decreased in many developed nations, it continues to pose a significant public health challenge in many developing countries [ 5 ]. In 2022, TB tragically claimed the lives of approximately 1.3 million people worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TB is a significant infectious disease that remains prevalent in resource-poor countries. While its incidence has decreased in many developed nations, it continues to pose a significant public health challenge in many developing countries [ 5 ]. In 2022, TB tragically claimed the lives of approximately 1.3 million people worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…An Indian study on splenic TB found that 62% of the cases were linked with pulmonary TB, and half of the patients were coinfected with HIV [ 6 ]. In immunocompetent patients, the spleen can become infected through trauma, as well as through hematogenous spread from the lungs in cases of miliary TB and from nearby organs [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation